Mortality and development in the ESCAP region: A review - Lado T. Ruzicka; Penelope S. Kane (Asia-Pacific Population Journal, 1986)
The influence of economic conditions on health and mortality has long been recognized, although originally the emphasis was probably more on the impact of economic hardships than on the effects of affluence. Irregularities in food supply were well known and reported in ancient records, which describe, for example, the impact of shortages on mortality.